2011
DOI: 10.4236/msa.2011.27109
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Mechanical and End-Use Properties of Natural Rubber Filled with Snail Shell Powder

Abstract: A series of natural rubber-snail shell powder vulcanizates were compounded on a two-roll mill, and moulded on a compression moulding machine. The mechanical and end-use properties of the natural rubber vulcanizates were investigated at snail shell powder contents, 0 to 20 pphr. The snail shell powder was characterized for filler properties and sieved to 0.075, and 0.30 μm particle sizes. Carbon black was used as the reference filler. Results showed that the tensile strength, modulus, elongation at break, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…This is a clear indication of reinforcement by the fillers. Similar observations have been reported by previous researchers (Igwe and Ejim, 2011;Okoh et al, 2014;Osabohien et al, 2015;Osabohien and Ojeifo, 2017).…”
Section: Physicomechanical Properties Of Snr 10 Vulcanizatessupporting
confidence: 93%
“…This is a clear indication of reinforcement by the fillers. Similar observations have been reported by previous researchers (Igwe and Ejim, 2011;Okoh et al, 2014;Osabohien et al, 2015;Osabohien and Ojeifo, 2017).…”
Section: Physicomechanical Properties Of Snr 10 Vulcanizatessupporting
confidence: 93%
“…Clay was used by Kim et al [6] to fill butadiene rubber and reported that the tensile strength and tear strength of the rubber/clay composites were 4.4 times, and 2 times greater than that of unfilled rubber, respectively. Igwe and Ejim [7] prepared a series of natural rubber-snail shell powder vulcanizates and reported that the hardness of the vulcanizates was marginally increased at high snail shell powder content. However, the specific gravity of the rubber vulcanizates increased with the increase in snail shell powder content.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon black has been the main filler incorporated in natural rubber during vulcanization. The properties imparted in vulcanized rubber by fillers depend on factors such as particle sizes, structure, physico-chemical nature, surface area and porosity of the fillers (Igwe and Ejim, 2011). Arroyo, et.al.…”
Section: Introductionmentioning
confidence: 99%
“…The agricultural wastes that have been used and reported include milled coconut fibre (Egwaikhide, et.al., 2007), seed shells of cherry (Osabohien and Egboh, 2007), cocoa pod husk, rubber seed shell, rice husk and palm kernel shell (Ogbeifun, et.al., 2010), carbonized bagasse (Osarenmwinda and Abode, 2010), snail shells (Igwe and Ejim, 2011), carbonized groundnut shell (Ayo, et.al., 2011), carbonized cassava peel (Ugbesie, et.al., 2011), bamboo fibre (Onyeagoro, 2012), defatted rice bran (Moonchai, et.al., 2012), carbonized coir (Aguele and Madufor, 2012), carbonized and uncarbonized dikanut shell pericap (Ekabafe, et.al., 2012), maize stalk (Chigondo, et.al., 2013), carbonized palm kernel shell husk (Egwaikhide, et.al., 2013).…”
Section: Introductionmentioning
confidence: 99%